(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
The investigations of magnesium based matrix reinforced with the TiO2 particles with various weight ratios of 2.5, 5, 7.5 and 10% are presented in this research paper. The purpose of this work is to elaborate the manufacturing processes of pure magnesium metal with the addition of Titanium oxide through the vacuum stir casting route with the use of Argon as shielding gas to prevent the oxidation.Â The prepared samples by stir casting are machined with EDM for conducting experiments. The parameters like density, hardness, tensile strength, ultimate tensile strength are evaluated by immersion test, Rockwell Tester and UTM respectively.Â The presence of particles in phase is examined by XRD analysis. The microstructural examinations of the obtained composite materials ensure that homogeneous distribution of the reinforcing particles in the magnesium matrix was revealed by SEM.Â The results proved that improvement ofÂ 24% in Hardness, 29.8 %in Ultimate tensile strength .